The Influence of The Marketing Mix on Customer Decisions to Choose Gold Savings at PT Pegadaian Branch of Pematangsiantar City in 2024 - Barus, Ben Setiawan; Sirait , Yesicha Triarni; Purba, Ayu Azzari; Panjaitan , Gabriel; Siburian, Maretta Selvana; Asnahwati, Asnahwati (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
This research aims to analyze the influence of the Marketing Mix on customers' decisions to choose gold savings, both partially and simultaneously at PT Pegadaian Pematangsiantar City Branch. The type of research used is quantitative descriptive. The population in this study were all customers who chose gold savings at PT Pegadaian Pematangsiantar City Branch and the sample size in this study was determined by making the population into a sample, so that the sample for this study was 50 respondents. The data source in this research is primary data using a research instrument in the form of a questionnaire. The data collection method used is survey research. This research uses multiple linear regression analysis for statistical analysis and the regression model has been tested first in the classic assumption test. The results of this research state that simultaneous testing shows that there is a significant influence of product, price, location and promotion together on customers' decisions to choose gold savings at PT Pegadaian, Pematangsiantar City Branch. In the calculated F test 591.371> F table 2.578739, with a significant value of 0.05, it was stated that there was a significant influence between the Marketing Mix on the Customer's Decision to Choose Gold Savings at PT Pegadaian Pematangsiantar City Branch. Multiple regression analysis shows that partially the consumer's decision to choose gold savings (Y) is significantly influenced by Product and Promotion, meanwhile price and location show that these variables have no significant partial influence (the value in the Sig. column is greater than 0.05 ).